Shoreline Changes and Coastal Evolution as Parameters to Identify Priority Areas for Management in Rio Grande do Sul, Brazil - ESTEVES, LUCIANA SLOMP (Pesquisas em Geociências, 2004)
About 80% of the Rio Grande do Sul coastline is undeveloped. The state Program of Coastal Management is incipient and has addressed only the northern coastal sector, which concentrates most of the developed beaches in the state. The central and southern coastal sectors show ideal conditions to the implementation of a regional management plan based on measures that regulate occupation and uses. This study identifies classes of management for RS beaches based on: (a) rates of population growth from 1991 to 2000, (b) intensity of beachfront development and the state of conservation of the beach system, (c) shoreline changes from 1997 to 2002, and (d) coastal evolution in the Holocene. Four classes of management are defined: (1) critical areas, are highly developed or show a recent trend of increasing population, are eroding or accreting with large magnitudes of shoreline changes, and require corrective measures; (2) priority areas, are low to moderately developed but show a potential for intensification of occupation and uses in the near future, are eroding and show large magnitudes of shoreline movements, they require urgent regulation to restrict development and uses; (3) areas of future concern, are not under pressure at present and consist of eroding shores located close to critical or priority areas, regulation measures are recommended, and (4) natural areas, are mainly preserved, eroding or accreting, with no signs of changes in the near future. About 198 km (32% of the RS coastal length) are classified as priority areas (located along the central sector), 178 km (29%) as natural areas (in the southern coast of São José do Norte and between Cassino and Albardão), 177 km (29%) as critical areas (northern sector, Cassino, and between Chuí and Hermenegildo), and 65 km (10%) as areas of future concern (beaches from Hermenegildo to Albardão).